Dual Legal Frameworks on Forced Child Intercourse: Harmonizing Islamic Criminal Law and State Law - Cahyani, Sri Indah (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2025)
This study analyzes legal enforcement regarding forced child intercourse, focusing on Decision Number 714/Pid.Sus/2023/PN Medan. Employing a normative juridical method, this research evaluates the disparity in sanctions between Indonesian Positive Law and Islamic Criminal Law. The findings reveal that the defendant's 7-year sentence, while legally valid under the Child Protection Act, fails to provide substantial justice given the victim's psychological trauma. From an Islamic perspective, the act constitutes zina muḥṣan. However, due to evidentiary challenges regarding ḥadd, the principle of maximum discretionary punishment (ta‘zīr al-quswā) applies, particularly since the offender is a maḥram (incestuous guardian). Islamic legal options include capital punishment, life imprisonment, and financial compensation (mahr al-mithl) for the victim. The study concludes that harmonizing positive law with Islamic principles of aggravated punishment is crucial to ensure proportional sanctions and comprehensive child protection.